Mediastinal teratoma - Syamsuwidayat Syamsuwidayat; Slamet I. Sampurno; I. Budiman; Noenoeng Rahajoe; I Made Nasar (Paediatrica Indonesiana, 1982)
A case of mediastinal teraloma accompanied by patent ductus arteriosus in a 3-year and 5-month-old girl is reported. She had been suffering from fever, productive cough and dyspnea since one year. The diagnosis is made after surgery with preoperative diagnosis of encapsulated empyema and patent ductus arteriosus.This shows the difficulties to diagnose mediastinal teratoma in this age group. Post operatively, her condition is markedly improved.